Analisis Skema Ponzi dalam Penipuan Investasi Berkedok Teknologi AI: Studi Kasus Xpertise Future Analytics Indonesia Tahun 2024 - Firmansyah, Heru; Supadiyanto (Jurnal Audiens, 2025)
Technological advances in the digital era have changed the way people invest, but have also been used for fraud, as in the case of PT Xpertise Future Analytics Indonesia (XFA AI). This company ran a Ponzi scheme with an invitation-based system and promises large profits. On September 13, 2024, XFA AI disappeared, making off with investors' money. This research aims to analyze company strategies in influencing victims and offer solutions to prevent similar cases. Data was collected through autoethnography, interviews, observation and documentation. The research results show that XFA AI uses a Ponzi scheme with an invitation-based system to recruit new investors. Companies influence victims through promises of huge profits that appeal to individuals with low financial literacy.